Upland rice genomic signatures of adaptation to drought resistance and navigation to molecular design breeding - Wang, Yulong; Jiang, Conghui; Zhang, Xingtan; Yan, Huimin; Yin, Zhigang; Sun, Xingming; Gao, Fenghua; Zhao, Yan; Liu, Wei; Han, Shichen; Zhang, Jingjing; Zhang, Yage; et al. (Wiley, 2024)
Upland rice is a distinctive drought‐aerobic ecotype of cultivated rice highly resistant to drought stress. However, the genetic and genomic basis for the drought‐aerobic adaptation of upland rice remains largely unclear due to the lack of genomic resources. In this study, we identified 25 typical upland rice accessions and assembled a high‐quality genome of one of the typical upland rice varieties, IRAT109, comprising 384 Mb with a contig N50 of 19.6 Mb. Phylogenetic analysis revealed upland and lowland rice have distinct ecotype differentiation within the japonica subgroup. Comparative genomic analyses revealed that adaptive differentiation of lowland and upland rice is likely attributable to the natural variation of many genes in promoter regions, formation of specific genes in upland rice, and expansion of gene families. We revealed differentiated gene expression patterns in the leaves and roots of the two ecotypes and found that lignin synthesis mediated by the phenylpropane pathway plays an important role in the adaptive differentiation of upland and lowland rice. We identified 28 selective sweeps that occurred during domestication and validated that the qRT9 gene in selective regions can positively regulate drought resistance in rice. Eighty key genes closely associated with drought resistance were appraised for their appreciable potential in drought resistance breeding. Our study enhances the understanding of the adaptation of upland rice and provides a genome navigation map of drought resistance breeding, which will facilitate the breeding of drought‐resistant rice and the “blue revolution” in agriculture.